Literacy of Sexual Harassment and Abuse Toward Adolescent Protection Behavior - Ananda Dwitha Yuniar; Ananda Nur Azahra; Adenia Qonitalillah; Anggaunitakiranantika (MUWAZAH : jurnal kajian gender, 2022)
Cases of sexual harassment in Indonesia are increasingly prominent in the media when victims speak publicly. KOMNAS Perempuan notes that the spectrum of sexual abuse against women has increased by 800%. This seems to be a reminder for us, especially the young generation, to have the knowledge and ability to protect behavior from sexual abuse. This study aims to measure the extent of literacy of sexual harassment and violence on the level of self-protection by adolescents (15 – 21). A total of 120 young people consisting of men and women have participated in the online survey. Two-stage regression data analysis was carried out to measure each item. The sexual abuse literacy items (x) consist of Functional Literacy, Socio-Cultural Practice Literacy, Intellectual Empowerment Literacy, and The protection ability items (y) self-efficacy and self-defense. The results show that the higher the literacy level of adolescents against sexual abuse and harassment, the more they will be able to protect behavior from various threats.